Progression of Bio-Tribocorrosion in Implant Dentistry - Dini, Caroline; Costa, Raphael C.; Sukotjo, Cortino; Takoudis, Christos G.; Mathew, Mathew T.; Barão, Valentim A. R. (Frontiers in Mechanical Engineering, 2020)
Oral rehabilitation devices are susceptible to bio-tribocorrosion phenomena in the oral environment due to the synergism of wear, chemical, biochemical, and microbiological processes. This review summarizes the clinical problems and advances obtained based on current scientific evidence as well as the influence of tribological fundamentals, testing methodologies and protocols in tribocorrosion analyses. The main clinical question related to oral rehabilitation with dental implants is the treatment failure, which is influenced by material degradation. Titanium-based implants are exposed to wear and corrosion challenges in the oral environment since the implantation and along the lifetime service. The titanium (Ti) properties such as structural material, connection design, surface treatments, alloying elements are influencing factors for material behavior. In addition, wear-corrosion factors such as cyclic loads, micromovements, oral biofilm, decontamination methods are also associated with dental implants degradation. These environmental conditions to which dental implants are submitted leads to the release of Ti particles and ions with cytotoxic and harmful effects on peri-implant surrounding tissues. In this context, the current state of the art of bio-tribocorrosion over the last decade has been steadily increasing to understand material degradation. The basic test system used to translate the tribocorrosion phenomena in the oral environment to the bench consists of electrochemical and tribological synergic analysis. The mechanical (applied load, frequency, stroke distance and number of cycles) and electrochemical (solution composition, concentration of anions and pH) test conditions are determinants for materials tribocorrosion performance. To overcome the tribocorrosion phenomena some strategies have been used such as alloying elements for Ti-alloys manufacture, surface treatments, and biomolecules immobilization. Further studies need to have the tribocorrosion analyses as the basis for new smart materials development considering the importance of such aspects for the biomaterial clinical behavior. Finally, tribological tests are relevant strategies for understanding the mechanisms of degradation in the oral environment and for providing a way to improve the clinical outcomes of dental implants.